2021
DOI: 10.1021/acs.jpcc.0c10340
|View full text |Cite
|
Sign up to set email alerts
|

Structural, Magnetic, and Electrical Properties of Doubly Ordered Perovskites NaLnNiWO6 (Ln = La, Pr, Nd, Sm, Eu, Gd, and Tb)

Abstract: We report the structural, magnetic, and electrical properties of a new family of doubly ordered perovskites NaLnNiWO6 (Ln = La, Pr, Nd, Sm, Eu, Gd, and Tb), synthesized at high-pressure (4.5 GPa) and high-temperature (1000 °C) conditions. These materials crystallize in the monoclinic structure with the polar space group P21 as revealed by neutron diffraction (Ln = La), X-ray diffraction, and second-harmonic-generation (SHG) studies. These compounds exhibit a combined layered ordering of A-site cations and rock… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 48 publications
0
8
0
Order By: Relevance
“…For formation of clear layered ordering, the charge separation at A- and B-sites plays an important role, as derived from ML models. These insights can be further validated by experimental studies on ordered double perovskites NaLnNiWO 6 , where Ln= La, Pr, Nd, Sm, Eu, Gd, and Tb . In this study, the authors have investigated theeffect of cationic charges on cation ordering.…”
Section: Resultsmentioning
confidence: 86%
See 3 more Smart Citations
“…For formation of clear layered ordering, the charge separation at A- and B-sites plays an important role, as derived from ML models. These insights can be further validated by experimental studies on ordered double perovskites NaLnNiWO 6 , where Ln= La, Pr, Nd, Sm, Eu, Gd, and Tb . In this study, the authors have investigated theeffect of cationic charges on cation ordering.…”
Section: Resultsmentioning
confidence: 86%
“…At its current stage, these data on different A-site cation ordering arrangements are not available in literature. Most of the experimental observations have reported compounds where A-site layered ordering is favorable. Thus, our computational data can become a good addition for further explorations. The study is intended to aid into interpretability as well as discovery of cause–effect relationships (going beyond the standard practices of ML to uncover structure–property relationships) between features representing cation ordering in double perovskites.…”
Section: Introductionmentioning
confidence: 81%
See 2 more Smart Citations
“…The neutron diffraction studies of NaYNiWO 6 revealed a spin density wave structure just below T N and transforms to a collinear structure below 18 K. 26 On the other hand, the doubly ordered perovskites NaLnMnWO 6 (Ln = La, Nd, and Tb), NaLnFeWO 6 (Ln = La, Nd, Pr, and Sm), and NaLnNiWO 6 (Ln = La, Pr, Nd, and Sm−Tb) did not exhibit any change in polarization below magnetic ordering temperature. 28,36,37 It could be due to a small polarization that is below the instrument's resolution limits. Theoretically, it has been studied that the compounds with lower size rare earth cations with increasing size difference at the A-site exhibit larger octahedral distortion, and hence, higher polarization is expected.…”
Section: Introductionmentioning
confidence: 99%